Ethylene Treated Kiwi Fruits during Storage. Part I: Postharvest Bioactive, Antioxidant and Binding Properties - Martin Polovka (2018)
© 2016 Wiley Periodicals, Inc. Kiwi fruits “Hayward” were submitted to ethylene treatment during 24 h, following by storage at 20C for 10 days. Significant differences were found in polyphenols and in the antioxidant capacities in conventional, low chemical and organic kiwi fruits. Ethylene treatment increased the bioactivity of organic, low chemical and conventional kiwi fruit. The antio xidant values for organic fruits were significantly higher than for conventional and nontreated samples. All investigated kiwi fruits showed a high level of correlation between the contents of phenolic compounds, their antioxidant and binding values. The statistical evaluation of bioactivity demonstrated that cultivation system and ethylene treatment following by storage have the potential to enhance the accumulation of health-beneficial food compounds in kiwi fruit and changes of the binding properties. Practical Applications: The article describes the impact of three treatments including different agricultural systems, ethylene treatment and storage and biochemical changes in kiwi fruit. Agricultural system produced three different kiwi fruits: organic, semi-organic and conventional. Different cultivation systems affect the polyphenols and antioxidant status of kiwi fruit. During the ethylene treatment and storage the antioxidant status and binding properties have increased. In general these treatments affect the contents of the main bioactive compounds which have high nutritional value. In practice we can select the best treatment and its duration in connection with the best quality of the final product. This could be of economical importance for the kiwi fruit industry in development of new products with long shelf life and high quality of the final product.